Oral Versus Gastrointestinal Mucosal Immune Niches in Homeostasis and Allostasis - Suárez, Lina J.; Arboleda, Silie; Angelov, Nikola; Arce, Roger M. (Frontiers in Immunology, 2021)
Different body systems (epidermis, respiratory tract, cornea, oral cavity and gastrointestinal tract) are in continuous direct contact with innocuous and/or potentially harmful external agents, exhibiting dynamic and highly selective interaction throughout the epithelia, which function as both a physical and chemical protective barrier. Resident immune cells in the epithelia are constantly challenged and must distinguish among antigens that must be either tolerated or those to which a response must be mounted for. When such a decision begins to take place in lymphoid foci and/or mucosa-associated lymphoid tissues, the epithelia network of immune surveillance actively dominates both oral and gastrointestinal compartments, which are thought to operate in the same immune continuum. However, anatomical variations clearly differentiate immune processes in both the mouth and gastrointestinal tract that demonstrate a wide array of independent immune responses. From single vs. multiple epithelia cell layers, widespread cell-to-cell junction types, microbial-associated recognition receptors, dendritic cell function as well as related signaling, the objective of this review is to specifically contrast the current knowledge of oral versus gut immune niches in the context of epithelia/lymphoid foci/MALT local immunity and systemic output. Related differences in 1) anatomy 2) cell-to-cell communication 3) antigen capture/processing/presentation 4) signaling in regulatory vs. proinflammatory responses and 5) systemic output consequences and its relations to disease pathogenesis are discussed.